Conservatism and Equity Ownership of the Founding Family - CHEN, Shuping (Institutional Knowledge at Singapore Management University, 2014)
We investigate the impact of founding family ownership on accounting conservatism. Family ownership is characterised by large, under-diversified equity stake and long investment horizon. These features give family owners both the incentives and the ability to implement conservative financial reporting to reduce legal liability and mitigate agency conflicts with other stakeholders. Since CEOs can have different incentives towards conservatism, we focus on ownership of non-CEO founding family members in our investigation. We find that conservatism increases with non-CEO family ownership, supporting our prediction. This relationship becomes insignificant in family firms with founders serving as CEOs, either due to founder CEOs' incentives to implement more conservative financial reporting or their power to thwart non-CEO family owners' demand for conservatism. Overall, our paper adds to the literature on the impact of founding family ownership on firms' financial reporting policy. Our findings are consistent with the recent evidence in the family-firm literature that founding families exhibit substantial incentives to reduce agency and litigation costs and to maximise firm value.